Occupational Health and Well-being Questionnaire (OHWQ): an instrument to assess psychosocial risk and protective factors in the workplace. (September 2022) - Truchon, M.; Gilbert-Ouimet, M.; Zahiriharsini, A.; Beaulieu, M.; Daigle, G.; Langlois, L.
Abstract: Objectives: Psychosocial stressors at work have been identified as significant risk factors for several mental and physical health problems. These stressors must be compensated by psychosocial resources to prevent or reduce adverse effects on health. Questionnaires measuring these stressors and resources already exist, but none integrate digital stress, ethical culture, and psychosocial safety climate; factors that are increasingly linked to workers' health. This study aims to develop and establish the psychometric properties of one of the most comprehensive instruments measuring the psychosocial work environment to date: the Occupational Health and Well-being Questionnaire (OHWQ). Study design: A cross-sectional validation study is proposed to develop the OHWQ and document its psychometric properties. Methods: The OHWQ was developed from validated instruments to which new items were added. The questionnaire includes psychosocial dimensions, along with indicators of psychological distress, musculoskeletal disorders, and well-being. It was administered to a sample of 2770 participants from a population working in the academic field. Exploratory and confirmatory factor analyses and the calculation of Cronbach's α coefficient were used to identify the variables, items, and, dimensions of the OHWQ and to document its main psychometric properties. Results: The acceptability of the measurement model was evaluated by the reliability of the items, internal consistency between the items, and the convergent and discriminant validity. Construct validity was assessed using exploratory and confirmatory factor analyses. Using factor analyses and cut-off rules, the new instrument has 124 items grouped into 22 dimensions. The OHWQ demonstrated satisfactory reliability and validity, as well as reasonable fit indices. The internal consistency of the scales was also good (Cronbach's α = 0.68–0.96, median = 0.85). Conclusion: The OHWQ demonstrated good psychometric properties. It could be useful for both research purposes and for workplaces interested in developing concrete action plans aimed at improving the balance between psychosocial work stressors and resources.